1993
DOI: 10.1103/physrevb.48.12063
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved electron-energy-loss study of Al/Si(111)

Abstract: We have performed a high-resolution electron-energy-loss study of the Si(111)-(~3x~3)R30':Al surface and have measured the dispersions of several surface phonons along the I'K direction. We interpret these using two different simple lattice dynamical models, both employing force constants from an ab initio electronic-structure calculation of Northrup. The first yields quantitative information at q = 0; the second is a semiquantitive estimate of the dispersion. These models have no adjustable parameters. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This study was restricted to zero momentum transfer (/_) and it was found that certain phonon energies were in agreement with calculations by Northrup [7]. Recently, we have measured the dispersion of these modes along a high symmetry axis (/_/() of the SBZ [8]. We have shown that by use of force constants from the ab initio electronic structure calculation of Northrup it is possible to account for the mode dispersion in a semi-_uantitative way, with no adjustable parameters.…”
Section: Copper-oxide Based High Temperature Superconductorssupporting
confidence: 70%
“…This study was restricted to zero momentum transfer (/_) and it was found that certain phonon energies were in agreement with calculations by Northrup [7]. Recently, we have measured the dispersion of these modes along a high symmetry axis (/_/() of the SBZ [8]. We have shown that by use of force constants from the ab initio electronic structure calculation of Northrup it is possible to account for the mode dispersion in a semi-_uantitative way, with no adjustable parameters.…”
Section: Copper-oxide Based High Temperature Superconductorssupporting
confidence: 70%
“…22 The mode is characteristic of the Si͑111͒ surface having T 4 adatoms. 23,24 As far as high-energy photoelectron is concerned, forwardscattering is dominant, and only the wave emitted toward the scatterer contributes to the intensity. Therefore, the parity of the photoelectron wave function has no influence upon the intensity distribution.…”
Section: Discussionmentioning
confidence: 99%